Strategi pengembangan obyek wisata Hutan Pinus To’Nakka Ulusalu Kecamatan Saluputti Kabupaten Tana Toraja - Tapparan, Samuel Randy; Rambulangi, Abedneigo Carter; Mantong, Agustinus; K. Pongtuluran, Althon (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the development strategy of the To’Nakka’ Ulusalu pine forest touristm object Saluputti sub-district Tana Toraja district. This type of research is descriptive qualitative research. The analytical method used is by using SWOT analysis. The data collection technique used in this research is to do documentation, observation and direct interviews with the manager of the To’Nakka’ Ulusalu pine forest tourism object. Based on the results in the research that has been done by researchers, As for the strategy for developing the To'Nakka Ulusaslu Pine Forest tourist attraction, namely: (1) Build partnerships/cooperation with local governments in the management of the Ulusalu To’Nakka’ pine forest tourism object Saluputti sub-district Tana Toraja district. (2) Provide adequate tourist facilities such as: improvement of access road, lodging, restaurants, and so on that can support the comform of visitors to tourist attractions. (3) Maximally promote the Ulusalu To’Nakka’ Pine forest tourism object through social media so that it can be widely known by the public.